Morphophysiological Plasticity in a Wheat Variety in Response to NaCl Stress and its Alleviation by Exogenous Abscisic Acid - Travaglia, Claudia Noemi (2013)
Nowadays, soil salinity is the most unfavourable abiotic factors for plant growth, causing important yield loss of many crops. A partial solution to this situation is to establish crop varieties in these areas affected which are tolerant to stress. The aim of this study was to evaluate in a wheat variety, the morphophysiological plasticity to sodium chloride (NaCl) stress and the effect of exogenous Abscisic Acid (ABA) on physiological variables. This was carried out by using the BI3000 wheat variety, for regional adaptability experiments. The germination percentage, coleoptile and radicle growth and root anatomic were evaluated, both seedling irrigated with water or saline solution. On the other hand, ABA sprays were applied to wheat plants and their biomass, pigment, stomatal behaviour and cellular membrane injuries were determined after salt treatments. In this study, it was possible to determine that the BI3000 wheat variety can grow in high electrical conductivity, with good germination and seedling growth. This variety showed less radical anatomic variations under salinity, what allows a faster plasticity to adapt. ABA applications suggest a protective role in plants under salinity, due to an increase in chlorophyll and carotene content, stability of cell membranes and stomatal behavior. This study is a contribution to a better understanding of the morphophysiological responses of glycophytic plants to salt stress. This have been pointed out as a useful approach to show more tolerance to salt stress crops in the future and it suggests that ABA could help improve agriculture production in areas affected by this stress.